2022
DOI: 10.1063/5.0071652
|View full text |Cite
|
Sign up to set email alerts
|

Viscous shaping of the compliant cell nucleus

Abstract: The cell nucleus is commonly considered to be a stiff organelle that mechanically resists changes in shape, and this resistance is thought to limit the ability of cells to migrate through pores or spread on surfaces. Generation of stresses on the cell nucleus during migration and nuclear response to these stresses is fundamental to cell migration and mechano-transduction. In this Perspective, we discuss our previous experimental and computational evidence that supports a dynamic model, in which the soft nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 48 publications
(53 reference statements)
2
29
0
Order By: Relevance
“…These differences in shape can be explained by a mechanical resistance to a strain of the nuclear interior on the shorter time scale but a uniform nuclear pressure balanced by surface tension on the longer time scale. This explanation is consistent with the notion that any mechanical energy stored in the strained nuclear interior dissipates on the time scale of migration such that only the surface tension and the resistance of the nucleus to volume change (i.e., nuclear pressure) govern nuclear deformation in response to external forces on this time scale (Lele et al, 2018, Dickinson et al, 2022).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…These differences in shape can be explained by a mechanical resistance to a strain of the nuclear interior on the shorter time scale but a uniform nuclear pressure balanced by surface tension on the longer time scale. This explanation is consistent with the notion that any mechanical energy stored in the strained nuclear interior dissipates on the time scale of migration such that only the surface tension and the resistance of the nucleus to volume change (i.e., nuclear pressure) govern nuclear deformation in response to external forces on this time scale (Lele et al, 2018, Dickinson et al, 2022).…”
Section: Resultssupporting
confidence: 87%
“…It is well known that on short time scales, nuclei can behave visco-elastically (Guilak et al, 2000, Dahl et al, 2005, Pajerowski et al, 2007, Ivanovska et al, 2010, Swift et al, 2013, Shin et al, 2013, Harada et al, 2014, Stephens et al, 2017, Wintner et al, 2020, Zuela-Sopilniak et al, 2020). However, we have previously shown that on the time scale of cell migration, nuclear deformations that occur during migration are not elastic ((Tocco et al, 2018) and reviewed in (Lele et al, 2018, Dickinson et al, 2022)). That is, deformed nuclear shapes in cells are not restored following the removal of cellular forces, suggesting that there is no storage of elastic energy in nuclear shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations